Environmental Knowledge, Awareness, and Business School Students’ Intentions to Purchase Green Vehicles in Emerging Countries - Mohiuddin, Muhammad; Al Mamun, Abdullah; Syed, Fazal; Masud, Muhammad Mehedi; Su, Zhan (MDPI, 2018)
Environmental awareness and changing attitudes toward "green consumption" are becoming evident in emerging countries' markets. Using an extended theory of planned behavior, this paper aims to examine emerging countries' business students' intentions to purchase green vehicles. Stratified random sampling was used to select study participants, and data were collected through face-to-face interviews. Results revealed that environmental knowledge and awareness have a significant influence on business students' favorable attitudes toward green vehicles. Further, a significant association between attitudes toward green vehicles, perceived behavioral controls, and intentions to purchase green vehicles was observed. Findings serve to inform managers and policy makers who are formulating strategies for maximizing value creation in an era of increasingly environmentally aware consumers in emerging markets. Ultimately, this policy will help to promote green technology initiatives, and encourage higher rates of adoption of eco-friendly vehicles in emerging countries.